A fresh perspective on an established marker: S100B‐dynamics for early detection of melanoma recurrence. (17th July 2020) - Posch, C.
Abstract : Linked article : S.S. Ertekin et al. J Eur Acad Dermatol Venereol 2020; 34:1482‐1488. https://doi.org/10.1111/jdv.16212 .